Guidelines of Handbook on Recruitment Rules 1996 - Government of India, Ministry of Personnel, PG and Pensions (Government of India, Ministry of Personnel, PG and Pensions, 1996)
The Handbook on Recruitment Rules 1996 provides comprehensive guidelines for framing, amending, and relaxing Recruitment Rules for all posts likely to last a year or more in the Central Government. It emphasizes immediate action by the Administrative Ministry/Department when creating or upgrading posts, ensuring proper Recruitment Rules or Service Rules are in place. Posts of shorter duration may be filled on deputation or re-employment of retired personnel, with direct recruitment permitted only under specific conditions. Approval of Recruitment Rules, including amendments, is generally at the Minister-in-charge level, with delegation allowed to Secretaries or Joint Secretaries for certain posts. Draft rules for Groups A and B posts require prior clearance from the Department of Personnel & Training (DOPT) and consultation with the Union Public Service Commission (UPSC), while Group C rules can be framed and relaxed by Ministries with DOPT concurrence in case of deviations. The guidelines also cover preparation of schedules, initial constitution of services, consideration of incumbents during upgradation, retention of existing eligibility service, and assessment of suitability where applicable. Recruitment Rules should be reviewed every five years to reflect changes in post strength and organizational requirements. A Saving Clause ensures that revisions do not affect reservations, age relaxations, or concessions for Scheduled Castes, Scheduled Tribes, ex-servicemen, and other special categories, maintaining compliance with central government orders.
Government of India, Ministry of Personnel, PG and Pensions, (Department of Personnel and Training)
Government of India, Ministry of Personnel, PG and Pensions, (Department of Personnel and Training)
Keywords: Recruitment Rules, Administrative Ministry, Deputation, Promotion, Eligibility Service, Organized Services, Initial Constitution, Upgradation, Draft Notification, Department of Personnel & Training, UPSC Consultation, Saving Clause